2019
DOI: 10.18404/ijemst.473605
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Alternatively Certified New High School Chemistry Teacher’s Assessment Literacy

Abstract: Assessing student learning to adapt instruction to support learning is an important skill all teachers need to develop. However, it is not an easy task for teachers and even more difficult for new teachers. The current study aims to explore an alternatively certified new chemistry teacher"s understanding and practices of classroom assessment to help educators and researchers to support teachers" assessment literacies. This study used holistic case study design to explore the teacher"s assessment literacy. Pre/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Results of the studies conducted with pre-service teachers revealed that although preservice teachers' assessment literacy was close to constructivist view, in theory, their assessment practices were more traditional. Studies conducted with in-service teachers yielded similar findings (Gottheiner & Siegel, 2012;İzci & Siegel, 2019). Content analysis of studies regarding assessment knowledge and practice (İzci, 2018) indicated that there have not been longitudinal studies on assessment literacy.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Results of the studies conducted with pre-service teachers revealed that although preservice teachers' assessment literacy was close to constructivist view, in theory, their assessment practices were more traditional. Studies conducted with in-service teachers yielded similar findings (Gottheiner & Siegel, 2012;İzci & Siegel, 2019). Content analysis of studies regarding assessment knowledge and practice (İzci, 2018) indicated that there have not been longitudinal studies on assessment literacy.…”
Section: Introductionmentioning
confidence: 78%
“…Some focused on the change in pre and in-service teachers' assessment literacy after participating in a professional development program or a course (DeLuca, Chavez, Bellara & Cao, 2013;Deneen & Brown, 2016;Koh, 2011) and relied on teachers' documents to reveal their assessment literacy without using observations. Other qualitative studies examined middle school science (Gottheiner & Siegel, 2012), chemistry (Izci & Siegel, 2019), pre-service physics (Ogan-Bekiroglu & Suzuk, 2014), and pre-service secondary (Siegel & Wissehr, 2011) teachers' assessment literacy during the planning and teaching a science topic. Even though there has been an increase in the number of research on assessment literacy relying on qualitative data, there has been scarcity of studies focusing on both knowledge and practice level of assessment literacy with its all dimensions (e.g., İzci, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instructors have varying experiences with assessment training, which can be formal or informal (Izci and Siegel, 2019;Schultz et al, 2018). Instructors' experiences of assessment training are likely influenced by their experiences of assessment as a student, their instructional experiences, talking with their peers, or formal professional development.…”
Section: The Instructor-as-assessor Identity Is Complex and Dynamicmentioning
confidence: 99%